An Innovative Framework for Sustaining High-Quality Customer Service During the Expansion of Small and Medium Enterprises - Borde, Sharad (Global journal of Business and Integral Security, 2024)
Small and medium enterprises (SME) are privately owned organizations. SMEs play an important role in the contribution of national economics. Around the world, SMEs contributes in many fields, especially in employing innovation mechanism in their organizations. To develop sustainable growth and enhance the revenue system, organizations strive to maintain their sustainable productivity. Additionally, the organizations are under pressure from the government sectors to generate high revenue and increase sustainable development. The main objective of the present study is to evaluate the significance of SMEs and their high-quality customer service in the expansion of SMEs. Additionally, it determines the factors affecting the SME to compete in the global market. It also examines the challenges faced by SMEs during its expansion. The present research executes a quantitative analysis utilizing the SPSS version 23 software package. A structured questionnaire survey technique is utilized to gather the data from the entrepreneurs in the SME sector. A purposive sampling strategy has been adopted for analysis. The objective behind the technique is to gather data relating to the perception of entrepreneurs regarding the expansion of their firms in the competing environment. Descriptive statistics, ANOVA, regression, and Pearson correlation analysis are performed in the research. The outcomes of the study revealed that the expansion of SMEs has a significant impact on firms' customer services. Furthermore, the study also evaluates the key factors affecting the expansion of SMEs. The study recommends that entrepreneurs enhance their strategies for increasing employee retention in the firms.